Morphology and dynamic scaling analysis of cell colonies with linear growth fronts - Huergo, María Ana Cristina (2010)
The growth of linear cell colony fronts is investigated from the morphology of cell monolayer colonies, the cell size and shape distribution, the front displacement velocity, and the dynamic scaling analysis of front roughness fluctuations. At the early growth stages, colony patterns consist of rather ordered compact domains of small cells, whereas at advanced stages, an uneven distribution of cells sets in, and some large cells and cells exhibiting large filopodia are produced. Colony front profiles exhibit overhangs and behave as fractals with the dimension DF=1.2560.05. The colony fronts shift at 0.2260.02 mm min−1 average constant linear velocity and their roughness swd increases with time std. Dynamic scaling analysis of experimental and overhangcorrected growth profile data shows that w versus system width l log-log plots collapse to a single curve when l exceeds a certain threshold value lo, a width corresponding to the average diameter of few cells. Then, the influence of overhangs on the roughness dynamics becomes negligible, and a growth exponent b =0.3360.02 is derived. From the structure factor analysis of overhang-corrected profiles, a global roughness exponent as=0.5060.05 is obtained. For l.200 mm, this set of exponents fulfills the Family-Vicsek relationship. It is consistent with the predictions of the continuous Kardar-Parisi-Zhang model.